Evaluation of 4‐(4‐Fluorobenzyl)piperazin‐1‐yl]‐Based Compounds as Competitive Tyrosinase Inhibitors Endowed with Antimelanogenic Effects. (26th July 2021) - Mirabile, Salvatore; Vittorio, Serena; Paola Germanò, Maria; Adornato, Ilenia; Ielo, Laura; Rapisarda, Antonio; Gitto, Rosaria; Pintus, Francesca; Fais, Antonella; De Luca, Laura
Abstract: There is a considerable attention for the development of inhibitors of tyrosinase (TYR) as therapeutic strategy for the treatment of hyperpigmentation disorders in humans. Continuing in our efforts to identify TYR inhibitors, we describe the design, synthesis and pharmacophore exploration of new small molecules structurally characterized by the presence of the 4‐fluorobenzylpiperazine moiety as key pharmacophoric feature for the inhibition of TYR from Agaricus bisporus (AbTYR). Our investigations resulted in the discovery of the competitive inhibitor [4‐(4‐fluorobenzyl)piperazin‐1‐yl]‐(3‐chloro‐2‐nitro‐phenyl)methanone 26 (IC50 =0.18 μM) that proved to be ∼100‐fold more active than reference compound kojic acid (IC50 =17.76 μM). Notably, compound 26 exerted antimelanogenic effect on B16F10 cells in absence of cytotoxicity. Docking analysis suggested its binding mode into AbTYR and into modelled human TYR. Abstract : The design, synthesis, and pharmacophore exploration of new molecules structurally characterized by the 4‐fluorobenzylpiperazine fragment are reported. Their inhibitory effects on Agaricus bisporus tyrosinase (AbTYR) were evaluated. Notably, the competitive derivative 26 revealed no cytotoxicity and exerted antimelanogenic effects on B16F10 cells. Docking analysis suggested its binding mode into AbTYR and into modelled human TYR.